Quantitative detection of siRNA and single-stranded oligonucleotides: relationship between uptake and biological activity of siRNA - Overhoff, Marita (Oxford University Press, 2004)
The quantitative detection of oligomeric nucleic acids including short double-stranded RNA in cells and tissues becomes increasingly important. Here, we describe a method for the detection of siRNA in extracts prepared from mammalian cells, which is based on liquid hybridization with a (32)P-labelled probe followed by a nuclease protection step. The limit of detection of absolute amounts of siRNA is in the order of 10–100 amol. This methodology is suited to quantitatively follow the spontaneous uptake of siRNA by mammalian cells, i.e. without the use of carrier substances. This protocol may also be used to detect extremely low amounts of other kinds of short nucleic acids, including antisense oligonucleotides.